2019
DOI: 10.1002/advs.201900177
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Methodology of Designing 3D SERS Probes with Superior Detection Limit and Uniformity by Maximizing Multiple Coupling Effects

Abstract: Accurate design of high‐performance 3D surface‐enhanced Raman scattering (SERS) probes is the desired target, which is possibly implemented with a prerequisite of quantifying formidable multiple coupling effects involved. Herein, by combining theory and experiments on 3D periodic Au/SiO 2 nanogrid models, a generalized methodology of accurately designing high performance 3D SERS probes is developed. Structural symmetry, dimensions, Au roughness, and polarization are successfully correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…[13,28] SPP Au-air and SPP Au-SiO2 (i.e., SPP PM-air and SPP PM-D -1) can interfere predominantly within the hexagonal air and SiO 2 wall cavities besieged by Au sidewalls via Fabry-Pérot (FP) resonance-like multiple reflections, respectively, as illustrated in Figure 1a; and Figure S1 of the Supporting Information. When the Au layer is thin (say, several nanometers only 20 ) enough, both SPP Au-air and SPP Au-SiO2 waves could transmit the Au layer into the SiO 2 and air cavities to be reflected by the opposite Au sidewalls, respectively, as shown in Figure 1. Without the transmission across the Au sidewall layers, the strongest interferences of SPP Au-air and SPP Au-SiO2 with their reflected waves can be achieved for L PM-D ≈ 302 nm and T D = 194 nm, i.e., integral multiple of half 𝜆 SPP Au-air and 𝜆 SPP Au-SiO2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,28] SPP Au-air and SPP Au-SiO2 (i.e., SPP PM-air and SPP PM-D -1) can interfere predominantly within the hexagonal air and SiO 2 wall cavities besieged by Au sidewalls via Fabry-Pérot (FP) resonance-like multiple reflections, respectively, as illustrated in Figure 1a; and Figure S1 of the Supporting Information. When the Au layer is thin (say, several nanometers only 20 ) enough, both SPP Au-air and SPP Au-SiO2 waves could transmit the Au layer into the SiO 2 and air cavities to be reflected by the opposite Au sidewalls, respectively, as shown in Figure 1. Without the transmission across the Au sidewall layers, the strongest interferences of SPP Au-air and SPP Au-SiO2 with their reflected waves can be achieved for L PM-D ≈ 302 nm and T D = 194 nm, i.e., integral multiple of half 𝜆 SPP Au-air and 𝜆 SPP Au-SiO2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, [20] SPPs interference intensities could be calculated in terms of the combination of quadrilateral and parallel-wall models, which was successfully extended to other multilateral structures. Similarly, two models, i.e., hollow square and parallel-wall Au/SiO 2 structures with smooth Au layers and H D = 228 nm derived from the maximum standing wave effects for a 632.8 nm wavelength shown in Figure 2a1, can be adopted for calculations of the interference intensities of SPP and EM waves at the sidewall surfaces against the thicknesses of Au layers and SiO 2 walls at both TM and TE modes, [20,32] as shown in Figure 2a2 [20] could be maximized at the thickness of about 7 nm Au, i.e., T PM = 7 nm, as seen in Figure S3b of the Supporting Information. This could be attributed to the combined effects from the EMFs confinement and the SPPs interferences.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 b shows the Raman signals for different concentrations of R6G induced by an excitation laser with a wavelength of 633 nm, which were collected to calculate the AEF using the following equation: AEF = ( I SERS / I OR )/( C SERS / C OR ), where I SERS and C SERS , and I OR and C OR correspond to the Raman intensities of R6G and the molar concentrations of the R6G solution on the SERS substrate and on the silicon wafer, respectively [ 24 ]. The AEF of R6G at 612 cm −1 was estimated to be 2.3 × 10 7 with the detection limit determined to be as low as 10 −9 M. The detection limit (signal/noise = 3/1) was defined as the lowest concentration that can be detected by spectrometer [ 25 , 26 , 27 ]. In addition, the SERS performance of the plasmonic superstructure arrays fabricated by single- and two-photo absorption were compared using R6G molecules at concentrations of 10 −7 M and 10 −8 M , which is shown in Supplementary Material, Figure S9 .…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al fabricated porous silicon photonic crystals for SERS by electrochemical anodization [40]. Tian et al demonstrated 3D SiO2 nano-grids for SERS substrates with maximizing multiple coupling effects by using electron-beam lithography [41]. Choi et al developed periodic MgF2 nanopillar arrays on a silicon wafer for highly reliable SERS substrates by combining nanoimprint lithography and electron beam evaporation [42].…”
Section: Introductionmentioning
confidence: 99%